Pengaruh Tingkat Penerapan Rencana Keselamatan Konstruksi Terhadap Risiko Kecelakaan Konstruksi - Magfira Lestaluhu; Albani Musyafa'; Edy Purwanto; Fitri Nugraheni (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to identify: (1) the level of implementation of the RKK; (2) the risk of construction accidents occurring on construction projects; and (3) the influence of the level of implementation of construction safety risks on construction safety. The research results show that (1) the level of implementation of the RKK in the IBS Building Construction project is stated to be in accordance with the provisions of these statutory regulations and is in accordance with Minister of PUPR Regulation No. 10 of 2021 amounted to 84.8% based on the results of the correlation test. (2) The risk of construction accidents occurring on the IBS Building Construction project includes structural work on reinforced concrete which is analyzed through 10 main provisions including implementing the K3 policy and guaranteeing commitment to implementing the K3 Management System; K3 policy stated in writing; adequate resources are available; an initial description of K3 conditions; Policy monitoring planning, goals and objectives for implementing the K3 management system; existence of planning regarding hazard elimination, risk assessment and control; an understanding of regulations and other requirements relating to K3; the establishment of policy goals and targets in the field of K3; the existence of K3 performance indicators that can be measured; and the existence of initial planning and planning of ongoing activities. (3) There is an influence between the level of implementation of construction safety plans on the risk of construction accidents on construction projects. This is shown by the calculated r value being greater than the table r value (0.848>0.521) and the significance value of 0.002 is less than 0.05 (0.002<0.05).